Implementasi Model JST Dalam Menentukan Bantuan Langsung Tunai Menggunakan Algortima Multilayer Perceptron Pada Desa Karang Anyar Kec. Aek Kuo - Nur Ainun; Rismayanti; Yuyun Dwi Lestari (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Direct cash assistance is cash assistance to poor families in KarangAnyar village, AekKuo sub-district. The government has carried out various ways to reduce poverty in addition to providing direct cash assistance. It can be seen considering the root of the problem, namely that almost all people do not have accurate data information about the condition of the problem and the potential data they have, therefore the government distributes cash direct assistance budgets. Where there are still distributions that are not right on target, as planned by the government. The programming system that will be used is Python by performing calculations using the Preceptron Multilayer algorithm artificial neural network method. Where there are already predetermined variables such as: salary income, status, and condition of the house, it will produce an output that predicts the receipt of direct cash assistance. This research is expected to be able to analyze the results of the population in KarangAnyar village, AekKuo sub-district, the problems that are in KarangAnyar village, AekKuo sub-district, so that the distribution of direct cash assistance remains the target